Knowledge and Awareness of Islamic Financial in Europe And America Countries - Ernawati Ernawati; Mansyur Asri (IQTISHADIA, 2020)
This study aims to determine the correlation between knowledge and awareness with industrial development, state religious status and state location. The data is sourced from secondary references of IFG-IFDI publication for the 2019 period on 42 countries in the European and American Continent. Data is processed through correlation analysis. The results show that  Islamic financial knowledge correlates with the level of scientific awareness.  Islamic financial knowledge and awareness of Islamic finance are positively correlated with the development of 4 (four) segments of Islamic finance, namely: Islamic banking, takaful, other Islamic finance, and sukuk; and does not correlate with the Islamic funds. The countries with a Muslim majority population will be more active in developing activities related to the Islamic financial industry.  There other side, there is no significant correlation between knowledge and awareness of Islamic finance with the continet location of the country. The research findings recommend an inclusive awareness movement so that it unites the academic and the public aspects in Islamic financial campaigns.